1984
DOI: 10.1111/j.1476-5381.1984.tb10786.x
|View full text |Cite
|
Sign up to set email alerts
|

Is Ro 03–7894 an irreversible antagonist at β‐adrenoceptor sites?

Abstract: 1 Ro 03-7894 (0.6 mM) produced a non-parallel shift to the right of dose-response curves to (-)-isoprenaline in K+ depolarized uterine preparations from the guinea-pig. The displacement of the curves was readily reversed by washing. A rightward shift of similar magnitude was also produced by Ro 03-7894 in transmurally stimulated ileal preparations. The relaxant effects of fenoterol in carbachol-contracted guinea-pig tracheal preparations (in the presence of 2 gM atenolol) were not altered by 0.6mM Ro 03-7894. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…However, to date no results have been described for the histamine H2receptor, presumably due to the lack of a specific compound that would satisfy all the criteria for being an irreversible H2-antagonist. Care must be taken to avoid compounds with a general non-specific depressant effect as recently reported for the P-adrenoceptor antagonist Ro 03-7894 on atrial preparations (Baker & Posner, 1983;Kostew et al,1984). Using the guineapig isolated right atrium, a tissue highly suited for the investigation of histamine H2-specific effects (Black et al.,1972), we have shown that the compound E1309 meets the necessary criteria.…”
Section: )mentioning
confidence: 55%
See 1 more Smart Citation
“…However, to date no results have been described for the histamine H2receptor, presumably due to the lack of a specific compound that would satisfy all the criteria for being an irreversible H2-antagonist. Care must be taken to avoid compounds with a general non-specific depressant effect as recently reported for the P-adrenoceptor antagonist Ro 03-7894 on atrial preparations (Baker & Posner, 1983;Kostew et al,1984). Using the guineapig isolated right atrium, a tissue highly suited for the investigation of histamine H2-specific effects (Black et al.,1972), we have shown that the compound E1309 meets the necessary criteria.…”
Section: )mentioning
confidence: 55%
“…The concepts of spare receptors and relative efficacy are now generally accepted (Kenakin, 1984;Ruffolo, (Baker & Posner, 1983;Kostew et al,1984). Using the guineapig isolated right atrium, a tissue highly suited for the investigation of histamine H2-specific effects (Black et al.,1972), we have shown that the compound E1309 meets the necessary criteria.…”
Section: Discussionmentioning
confidence: 82%
“…The estimation of KA by Furchgott's method would indeed be invalid as McPherson et al (1983) point out, but the result should be associated with a particular system rather than with a general principle that the method is invalid other than for hyperbolic curves. Indeed, since their initial study using Ro 03-7894, the same workers have questioned the classification of this compound as an irreversible, b-adrenoceptor antagonist (Krstew et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis implies that gradients for pre-and post-inactivation curves should only remain unchanged by [R0] (1983) point out, but the result should be associated with a particular system rather than with a general principle that the method is invalid other than for hyperbolic curves. Indeed, since their initial study using Ro 03-7894, the same workers have questioned the classification of this compound as an irreversible ,-adrenoceptor antagonist (Krstew et al, 1984).…”
Section: Discussionmentioning
confidence: 99%